Study of ready to use onion paste for prolonged shelf life (Progressive Agriculture, 2019)
This paper attempts to show the effect of preservatives and storage on the chemical, sensorial and microbial aspect of ready to use (RtU) onion paste, stored at two conditions i.e. ambient temperature (AT: 30±30C) and refrigerated temperature (RT: 5±10C) over a period of 180 days after treating with preservatives i.e. Potassium metabisulphites (KMS), Sodium benzoate (SB) and Citric acid (CA) at two levels i.e. 750 and 1000 ppm respectively. In the context of chemical aspect, a throughout observations over 180 days with 60 days interval showed negligible changes in chemical constituents of RtU onion paste both at AT and RT conditions with a little exception. Over the period pH slightly increased for both the storage conditions. Towards the sensorial point of view, use of preservatives in RtU onion paste resulted in the acceptance of color, flavor and texture up to 60 and 120 days of storage at AT and RT, respectively. To improve the effect of preservatives, mixture of them (KMS & CA; SB & CA) was also applied into to the sample (onion paste) besides the individual application. As a consequence, sensorial quality was better sustained by the addition of CA (0.8%) with other preservatives in comparison to the samples without CA. Onion paste, in specific, treated with 1000 ppm KMS & 0.8% citric acid stored both at AT and RT condition retained the most acceptable quality attributes compared to other treatments. However, onion paste without any preservative (control) was found acceptable only up to 20 days of storage at RT while storage at AT condition resulted in the more worse situation (acceptable up to 5 days). Total bacterial count was found in the lowest amount in RtU onion paste treated with the combination of KMS (1000 ppm) and CA (0.8%).Progressive Agriculture 30 (2): 219-226, 2019